Goodness-of-fit tests based on sample space partitions: a unifying overview. Issue 4 (2002) - Thas, O.; Ottoy, J. P.
Abstract : Recently the authors have proposed tests for the one-sample and theκ -sample problem, and a test for independence. All three tests are based on sample space partitions, but they were originally developed in different papers. Here we give an overview of the construction of these tests, stressing the common underlying concept of "sample space partitions."